Isu-isu Pendidikan di Indonesia Abad ke-21 Paradigma Desain Pembelajaran Mendalam (Deep Learning) - Jamaludin, Muhamad Samsul (Indo-MathEdu Intellectuals Journal, 2025)
Twenty-first century education requires learners not only to master content but also to develop critical thinking, creativity, collaboration, communication, and ethical as well as social awareness. This study aims to examine major issues in Indonesian education, particularly digital transformation, commercialization, and inclusivity, also to analyze deep learning design as a strategic response. The method employed is a literature review of recent studies and policy analyses related to digital education, pedagogical approaches, and inclusive practices. Findings reveal that digitalization expands opportunities for collaborative learning but is hindered by teachers’ low digital literacy, uneven infrastructure, and ethical concerns. Commercialization generates inequality due to high costs and market-oriented practices, while inclusive education struggles with limited trained personnel and adaptive facilities. Deep learning emerges as an alternative by emphasizing meaningful, reflective, differentiated, and collaborative learning experiences. It positions students as active subjects, integrates technology as a learning ecosystem, and reorients education toward its humanistic mission. Thus, deep learning design has the potential to serve as a transformative paradigm to address twenty-first century educational challenges in Indonesia and foster a more equitable, relevant, and sustainable system.